The Contents of Financial Statements of Public Finance Sector Units - Wrona, Bartłomiej; Rechul, Halina; Szulc, Małgorzata (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2018)
In the majority of countries, the finance sector constitutes one of the most important parts of the economy. Public finance sector units often raise funds and spend them on non-profitable activities, however essential they may be for the proper functioning of society. The cash participating in these operations make up a significant share of the transfers of a country’s entire economy. Thus, public finance sector units are required to keep books of account based on the provisions of the Accounting Act and specific legislation adapted to the specificities of the public finance sector. One of the obligations laid down by the Accounting Act is to present financial and property standing in the form of financial statements. As far as public finance sector units are concerned, the obligation has been extended to include preparation of budget reports, the main aim of which is to present a unit’s current situation with respect to its budget revenues and expenditures. The budget reporting system is currently used in the financial management of public finance sector units mainly in the short term. Financial statements, which may be the subject of financial analysis and support long-term decision making, have rarely been used. The paper presents financial reporting of public finance sector units, the possibilities of using the International Public Sector Accounting Standards (IPSAS) in accounting, and certain aspects of financial analysis and its use.